2019
DOI: 10.1111/nph.15878
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid signalling mediates biomass trade‐off and allocation in poplar

Abstract: Summary Abscisic acid (ABA) is a well known stress hormone regulating drought adaptation of plants. Here, we hypothesised that genetic engineering of genes involved in ABA stress signalling and photoperiodic regulation affected drought resistance by trade‐off with biomass production in perennial poplar trees. We grew Populus tremula × tremuloides wild‐type (T89) and various transgenic lines (two transformation events of 35S::abi1‐1, 35S::RCAR, RCAR:RNAi, 35S::ABI3, 35S::AREB3, 35S::FDL1, FDL1:RNAi, 35S::FDL2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 76 publications
1
31
0
Order By: Relevance
“…ABA plays a key role in plant stress resistance and the regulation of storage organ and root development, and is closely linked to N signaling (Kiba et al, 2011;Yu et al, 2019). In our study, the upregulated expression of ABA biosynthesis genes might explain why the ABA content of BF sweetpotato was 2-3 times that of CK sweetpotato (Figures 8E, 9).…”
Section: Increased Phytohormones Promoted the Formation Of Sweetpotatmentioning
confidence: 59%
“…ABA plays a key role in plant stress resistance and the regulation of storage organ and root development, and is closely linked to N signaling (Kiba et al, 2011;Yu et al, 2019). In our study, the upregulated expression of ABA biosynthesis genes might explain why the ABA content of BF sweetpotato was 2-3 times that of CK sweetpotato (Figures 8E, 9).…”
Section: Increased Phytohormones Promoted the Formation Of Sweetpotatmentioning
confidence: 59%
“…Eight of them were upregulated upon exogenous ABA treatment, whereas the other six members were downregulated (Ji et al, 2013). Transgenic plants overexpressing PtrAREB3 showed a strong drought tolerance phenotype under drought conditions with compromised biomass production (Yu et al, 2019). PeABF3, isolated from Populus euphratica, was induced by dehydration and ABA treatment.…”
Section: Arebs/abfsmentioning
confidence: 99%
“…This suggests that ABA-induced stomatal closure may be an important drought tolerance mechanism in Populus, a result supported by the findings of Brunetti et al 2019, who demonstrated a tight link between ABA-related gene expression and altered photosynthesis and stomatal conductance in response to drought in this bioenergy tree. The overwhelming impact of ABA control on biomass production was also demonstrated with a range of transgenic poplars grown outdoors (Yu et al, 2019). From these and other findings, a list of key phenotypic traits that are tractable in very large populations of bioenergy crops and underpin the drought tolerance ideotype have been identified and are summarized in Table 2.…”
Section: Developing An Ideotype For Drought Tolerance: Understanding mentioning
confidence: 93%